Prevalence of psychosis in black ethnic minorities in Britain: analysis based on three national surveys - Qassem, Tarik (Soc Psychiatry Psychiatr Epidemiol, 2014)
PURPOSE: A considerable excess of psychosis in black ethnic minorities is apparent from clinical studies, in Britain, as in other developed economies with white majority populations. This excess is not so marked in population surveys. Equitable health service provision should be informed by the best estimates of the excess. We used national survey data to establish the difference in the prevalence of psychosis between black ethnic groups and the white majority in the British general population. METHODS: Analysis of the combined datasets (N = 26,091) from the British national mental health surveys of 1993, 2000 and 2007. Cases of psychosis were determined either by the use of the Schedules for Clinical Assessment in Neuropsychiatry (SCAN), or from a combination of screening items. We controlled for sex, age, social class, unemployment, design features and other putative confounders, using a Disease Risk Score. RESULTS: People from black ethnic minorities had an excess prevalence rate of psychosis compared with the white majority population. The OR, weighted for study design and response rate, was 2.72 (95 % CI 1.3–5.6, p = 0.002). This was marginally increased after controlling for potential confounders (OR = 2.90, 95 % CI 1.4–6.2, p = 0.006). CONCLUSIONS: The excess of psychosis in black ethnic minority groups was similar to that in two previous British community surveys, and less than that based on clinical studies. Even so it confirms a considerable need for increased mental health service resources in areas with high proportions of black ethnic minority inhabitants.